Evaluation of the Progressivity Parameters of Chronic Kidney Disease after Branched-Chain Amino Acid Supplementation in Children - Esthy Poespitaningtyas; Roedi Irawan; Ninik Asmaningsih Soemyarso; Jusak Nugraha (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Chronic Kidney Disease (CKD) is not an uncommon issuein children. Chronic kidney disease is the abnormality of structure or function of the kidney that occurs for more than three months. The presence of a longitudinal decline in Glomerulus Filtration Rate (GFR), proteinuria, and hypertension Are the characteristics of CKD. One of the recommendations of nutritional supplementation as the prevention of CKD is by the administration of oral Branched-Chain Amino Acid (BCAA). To date, there has been no research to analyze the effects of the BCAA on children with stage 2-4CKD. This study aimed to analyze the effect of BCAA in inhibiting the progressivity of stage 2-4 CKD in children and improving nutritional status. A study with randomized pre-post test controlled trial design was performed in the Outpatient Clinic of Pediatric Nephrology in Dr. Soetomo Hospital with stage 2-4CKD. The subjects were divided into two groups, such as the BCAA and placebo, and were monitored for eight weeks to be evaluated the GFR, albumin, proteinuria, blood pressure, and nutritional status.Sixteen children with stage 2-4 CKD dominated by 71.4% of male patients were enrolled in this study. The mean age was 12.5 (SD 2.90) years. Approximately 50% (p=0.767) stage 2 chronic kidney, 50% (p=1.000) moderate malnutrition, and 64.28% (p=1.000) short stature were found, with nephrotic syndrome as the most common underlying cause of CKD (p=0.149). In BCAA group, decrease of GFR -5.08±7.13 (p=0.055), increase of serum albumin 0.20±0.23 (p=0.062), decrease of delta systole -11.57±15.08 (p=0.565) and diastole -4.85±16.25 (p=0.708), weight loss -0.07±1.01 (p=0.828), an increase of height 0.14±0.24 (p=0.771), and a decrease in BMI -0.03±0.74 (p=0.389) were reported. It was concluded that branched-chain amino acid (leucine, isoleucine, and valine) supplementation did not provide a significant effect to inhibit progressivity of stage 2-4CKD in children and improvement of nutritional status.